Investment and land disputes in Tanzania: a vehicle for investment legal reform - Lendita, Simon Wilson (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirement for award of Degree Master of Laws in Commercial law of Mzumbe University.